Nanobionics: A Sustainable Agricultural Approach towards Understanding Plant Response to Heavy Metals, Drought, and Salt Stress - Faizan, Mohammad; Karabulut, Fadime; Alam, Pravej; Yusuf, Mohammad; Tonny, Sadia Haque; Adil, Muhammad Faheem; Hayat, Shamsul (Mdpi, 2023)
In the current scenario, the rising concentration of heavy metals (HMs) due to anthropogenic activities is a severe problem. Plants are very much affected by HM pollution as well as other abiotic stress such as salinity and drought. It is very important to fulfil the nutritional demands of an ever-growing population in these adverse environmental conditions and/or stresses. Remediation of HM in contaminated soil is executed through physical and chemical processes which are costly, time-consuming, and non-sustainable. The application of nanobionics in crop resilience with enhanced stress tolerance may be the safe and sustainable strategy to increase crop yield. Thus, this review emphasizes the impact of nanobionics on the physiological traits and growth indices of plants. Major concerns and stress tolerance associated with the use of nanobionics are also deliberated concisely. The nanobionic approach to plant physiological traits and stress tolerance would lead to an epoch of plant research at the frontier of nanotechnology and plant biology.
Keywords: heavy metal; nutritional demands; physiological traits; nanotechnology